2014
DOI: 10.1186/s13068-014-0128-4
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the soybean transcription factor GmDof4 significantly enhances the lipid content of Chlorella ellipsoidea

Abstract: BackgroundThe lipid content of microalgae is regarded as an important indicator for biodiesel. Many attempts have been made to increase the lipid content of microalgae through biochemical and genetic engineering. Significant lipid accumulation in microalgae has been achieved using biochemical engineering, such as nitrogen starvation, but the cell growth was severely limited. However, enrichment of lipid content in microalgae by genetic engineering is anticipated. In this study, GmDof4 from soybean (Glycine max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 53 publications
2
49
0
Order By: Relevance
“…[83] GmDof4 significantly up-regulated ACCase activity and increased lipid content by up to 52% in transgenic microalgae C. ellipsoidea. [64] Synthetic soybean Dof-like TFs elevated the expression of genes involved in FA, phospholipid and glycolipid biosynthesis, such as enoyl-ACP-reductase, KASII, sulfolipid synthase, and MGD1 in transgenic C. reinhardtii. [84] …”
Section: Wrinkledmentioning
confidence: 98%
See 1 more Smart Citation
“…[83] GmDof4 significantly up-regulated ACCase activity and increased lipid content by up to 52% in transgenic microalgae C. ellipsoidea. [64] Synthetic soybean Dof-like TFs elevated the expression of genes involved in FA, phospholipid and glycolipid biosynthesis, such as enoyl-ACP-reductase, KASII, sulfolipid synthase, and MGD1 in transgenic C. reinhardtii. [84] …”
Section: Wrinkledmentioning
confidence: 98%
“…[61,62] Recently, characterization of basic leucine zippers (bZIPs), DNA binding with one finger (Dof) and MYB TFs further revealed their functions in lipid accumulation. [63,64] All these genes are expressed primarily or specifically during seed development and have a significant impact on seed oil production (Supplemental data Table 2). …”
Section: Role Of Transcriptional Regulation In Lipid Accumulationmentioning
confidence: 99%
“…To exploit the full potential of transcription factor targeted approaches, it is worthy to consider the transcription regulators of plant origin, in microalgal application for the regulation of lipid biosynthetic pathway. For instance, a significant enhancement of lipid content in Chlorella ellipsoidea was observed when Soybean GmDof4 transcription factor that affects lipid accumulation in Arabidopsis was overexpressed in the alga [114]. Other similar transcription factors regulating lipid metabolism have been studied and characterized in plants, few of which are described below.…”
Section: Constitutive Expression Of Transcription Regulators Involvedmentioning
confidence: 96%
“…It has been reported that nitrogen‐responsive regulator and phosphorous starvation response 1 (PSR1) TFs play important roles in lipid accumulation (Bajhaiya, Dean, Zeef, Webster, & Pittman, ; Boyle et al, ). Other studies reported an increased lipid content in Chlamydomonas and Chlorella cells that overexpressed DNA binding with one finger (Dof)‐type TFs (Ibanez‐Salazar et al, ; Zhang et al, ). In addition, we reported that the biomass and lipid production could be improved by the overexpression of stress‐ and/or lipid‐related TFs, including Nannochloropsis salina by overexpressing a basic helix‐loop‐helix transcription factor (NsbHLH2), AtWRI1, and NsbZIP1 (Kang et al, ; Kang et al, ; Kwon et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that nitrogen-responsive regulator and phosphorous starvation response 1 (PSR1) TFs play important roles in lipid accumulation (Bajhaiya, Dean, Zeef, Webster, & Pittman, 2016;Boyle et al, 2012). Other studies reported an increased lipid content in Chlamydomonas and Chlorella cells that overexpressed DNA binding with one finger (Dof)-type TFs (Ibanez-Salazar et al, 2014;Zhang et al, 2014).…”
mentioning
confidence: 99%